Role of Perceived Management Support and Personal Valence in Promoting Behavioral Support for Change: A Social Exchange Theory Perspective - Farhan Mehboob; Noraini Othman (STIM LASHARAN JAYA MAKASSAR, 2020)
Individuals’ support for change is a critical success factor to effectively implement change. Therefore, identifying the possible antecedent and mechanism leading to one’s behavioural support towards change is necessary. The study aims to unfold this avenue of research empirically by examining the role of both person and context factor in promoting behavioral support for change. Data was collected from 292 academic staff of six public sector universities in Pakistan via cross-sectional mean. A self-reported questionnaire was used to collect responses from the desired sample. SPSS 25 and AMOS were used to analyse the data for its relevance to study’s objectives. Results revealed a positive impact of perceived management support on academic staff’s behavioural support for change. Moreover, personal-valence provides an effective intervening mechanism to translate the effect of perceived management support on both dimensions of behavioural support for change such as compliance and championing behaviour. The study contributes to the existing literature on organizational change particularly to the university settings by examining and empirically validating both person and context factor as significant predictors to academic staff’s behavioral support for change.